Assessing dance: A phenomonological study of formative assessment in dance education - Andersson, Ninnie (Nordic Journal of Art & Research, 2014)
This article includes a study that examines how formative assessment in dance education is constituted in three Swedish upper secondary schools. The starting-point for the study is life-world phenomenology.  A phenomenological way of thinking entails that the human being is intersubjective, linked with and within the world and that learning requires the bodily subject´s active experience. To turn towards the things themselves and to be open and adherent to things in the world is a basic rule and the starting point for research within phenomenology. This study is based on empirical material from observations of the phenomenon formative assessment in dance. Spiegelberg´s philosophical method was used as a base for phenomenological analysis. The analysis results in three themes: modes of communication, dance-related knowledge and function of formative assessment. Formative assessment was observed in the study to commonly involve teachers´ verbal communication and visualisation. The assessment practice is a continuous activity and very rarely involves any kind of self-assessment or tests. The results were discussed and related to a life-world phenomenological view of learning and earlier research.